Measurement of CP observables in B±→D(*)K± and B±→D(*)π± decays using two-body D final states - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2021)
Measurements of CP observables in B± → D(*)K± and B± → D(*)π± decays are presented, where D(∗) indicates a neutral D or D∗ meson that is an admixture of meson and anti-meson states. Decays of the D(∗) meson to the Dπ0 and Dγ final states are partially reconstructed without inclusion of the neutral pion or photon. Decays of the D meson are reconstructed in the K±π∓, K+K−, and π+π− final states. The analysis uses a sample of charged B mesons produced in proton-proton collisions and collected with the LHCb experiment, corresponding to integrated luminosities of 2.0, 1.0, and 5.7 fb−1 taken at centre-of-mass energies of 7, 8, and 13 TeV, respectively. The measurements of partially reconstructed B± → D(*)K± and B± → D(∗)π± with D → K∓π± decays are the first of their kind, and a first observation of the B± → $$ {\left(Dπ^0\right)}_{D^{* }}{π}^{± } $$decay is made with a significance of 6.1 standard deviations. All CP observables are measured with world-best precision, and in combination with other LHCb results will provide strong constraints on the CKM angle γ.
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, G. Frau, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, H. Malygina, J. Marks, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, A. Zhelezov [und viele weitere]
Gesehen am 11.06.2021
Im Titel ist "±" und "(*)" jeweils hochgestellt